PENATAAN KAWASAN WISATA PULAU PARI DENGAN KONSEP ECOTOURISM - Bram Benjamin; Priyendiswara Agustina Bela (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2020)
Pari Island is one of the tourist islands in the Thousand Islands, Kepulauan Seribu Selatan, DKI Jakarta. The Thousand Islands is a region of marine tourism planning and development within the RIPPARDA (Planning Regional Tourism Development Master) based on the Jakarta Regional Regulation as a tourism area developed in Wonderful Indonesia. Pari Island is unique in its tidal phenomenon which is an attractive tourist point there, with the characteristics of limestone sand beaches. Other potentials and attractions also exist in customs in the Pari Island village, where many residents from outside the island carry customs them and mixed into unique behavioral customs. The author processes the data using analyzes that determine the arrangement of tourism areas on Pari Island where they want to be taken, using policy analysis, location analysis, site analysis, ecotourism concept analysis, best practice analysis, analysis tourism activities, market analysis, analysis of space requirements. The results of this plan are the arrangement of the Pari Island Tourism Area with the Ecotourism Concept. The plan also uses the concept of ecotourism which is certainly in accordance with the data and analysis conducted by the author to develop Pari Island as a good tourist location as a leading tourist site for Wonderful Indonesia. Potential arrangement that is good is the addition of restaurants, restaurants with a concept to relax and enjoy the view of the north coast of Pari Island. Tourism should have an awareness of the importance of environmental sustainability that can only be prevented by the visitor's self-awareness, facilities are well provided, only its use should be more more attention to the arrangement of the Pari Island Tourism Region is successful. Keywords: Ecotourism; Island Tourism Area; Small Island Tourism ABSTRAKPulau Pari adalah salah satu pulau wisata di Kepulauan Seribu, Kepulauan Seribu Selatan, DKI Jakarta. Kepulauan Seribu merupakan wilayah perencanaan dan pembangunan wisata bahari di dalam RIPPARDA (Rencana Induk Pembangunan Kepariwisataan Daerah) berdasarkan Perda DKI Jakarta sebagai kawasan pariwisata yang dikembangkan dalam Wonderful Indonesia. Pulau Pari memiliki keunikan pada fenomena pasang surut-nya yang menjadi titik wisata menarik disana, dengan karakteristik pantai yang pasir kapur.Potensi dan daya tarik lain juga ada di adat istiadat di kampung Pulau Pari, dimana warga banyak yang dari luar pulau yang membawa adat istiadat mereka dan tercampur menjadi adat istiadat perilaku yang unik.Penulis mengolah data dengan menggunakan analisis-analisis yang menentukan penataan kawasan wisata di Pulau Pari mau dibawa kemana, dengan menggunakan analisis kebijakan, analisis lokasi, analisis tapak, analisis konsep ekowisata, analisis best practice, analisis kegiatan wisata, analisis pasar, analisis kebutuhan ruang.Yang dari itu menghasilkan rencana penataan kawasan wisata Pulau Pari dengan konsep ekowisata.Rencana tersebut juga menggunakan konsep ekowisata yang tentunya sesuai dengan data dan analisis yang dilakukan penulis untuk mengembangkan Pulau Pari menjadi lokasi wisata yang baik sebagai lokasi wisata unggulan Wonderful Indonesia. Penataan yang berpotensi baik adalah penambahan rumah makan, restoran dengan konsep untuk bersantai menikmati pemandangan pesisir utara Pulau Pari. Wisatawan harus memiliki kesadaran akan pentingnya kelestarian lingkungan yang hanya dapat dicegah dengan kesadaran diri pengunjungnya, fasilitas sudah disediakan dengan baik, hanya penggunaannya saja yang harus lebih lagi diperhatikan agar penataan Kawasan Wisata Pulau Pari ini berhasil dengan baik.